Analytical View of the Satisfaction of Business Managers with the Career Management Process in International Companies - COCUĽOVÁ, Jana; TOMČÍKOVÁ, Ľuba (Journal of Advanced Research in Management; Vol 9 No 2 (2018): JARM Volume IX Issue 2(18) Winter 2018, 2019)
The process of career management as well as success criteria vary from person to person. The current understanding of career is characterized by a low degree of structuring, frequent job changes, sometimes changes of the profession. A higher degree of autonomy and individual responsibility for decision-making is important for one’s career growth. Flexibility and activity throughout the career is crucial. The role of a company is therefore to enable and, where appropriate, guide this process as well as the course of the career management. The aim of the paper is to analyze and evaluate the degree of satisfaction with individual career forming practices in business managers working in international companies with branches in the Slovak Republic.